Influence of social desirability on age differences in self-reports of mood and personality - Soubelet, Andrea (2011)
Increased age has been found to be associated with differences in affect and personality which have been interpreted in terms of better emotional regulation and increased maturity. However, these findings have largely been based on self-report data, and the primary goal of the current research was to investigate the hypothesis that age-related differences in affect and in certain desirable personality traits might, at least partially, reflect age differences in social desirability. As expected, increased age was associated with lower levels of negative affect and neuroticism and higher levels of positive affect, life satisfaction, agreeableness and conscientiousness, and scores on the social desirability scale were positively related to age and to desirable self-report characteristics, but negatively related to undesirable self-report characteristics. Importantly, controlling for the variance in the social desirability measure resulted in less positive age trends in both types of self-report measures.